Engineering Layered Nanostructures of Two-Dimensional Transition Metal Dichalcogenides with CeO2 for Nano-Level Detection of Promethazine Hydrochloride. Issue 7 (5th July 2021) - Selvi, Subash Vetri; Nataraj, Nandini; Chen, Tse-Wei; Chen, Shen Ming; Wu, Wei-Ling; Tseng, Tien-Wen; Huang, Chih-Ching
Abstract : Transition metal dichalcogenides (TMC) are utilized in diverse applications due to their 2D structure and effective tendencies. Molybdenum disulfide (MoS2 ) based TMC is emphasized for its lamellar structure with enormous edges which afford faster transfer of electrons for detecting molecules. To promote the action of conductance of MoS2, metal oxide can be employed and cerium oxide (CeO2 ) with abundant distinguishable properties was embedded with MoS2 . The nanocomposite MoS2 /CeO2 was characterized for structural and functional analysis by X-ray diffraction, Raman, and Fourier infra-red spectroscopy, resulting in the pure presence of MoS2 /CeO2 without additional constituent peaks. CeO2 nanorods embedded over MoS2 nanosheets were identified with field-emission scanning electron microscopy and their elemental presence identified with X-ray photoelectron spectroscopy and EDAX analysis. When fabricated over glassy carbon electrode (GCE) MoS2 /CeO2 showed superior conductivity facilitated by the higher active sites provided by MoS2 /CeO2 toward promethazine hydrochloride (PZC) oxidation. The resistance of the designed MoS2 /CeO2 electrode, ∼61 Ω, is attributed to the synergetic conducting behavior. The stability of the electrode was consistent with the similar current response over 20 days. When used for real-time detection in biological samples, the MoS2 /CeO2 /GCE established excellent response and a detection limit at 3 nM for the linear range from 0.009–695 μ M was obtained.